Media-related or generic-related features in electronic dictionaries: learners’ perception and preferences - Tan, Kim Hua; Woods, Peter Charles (Penerbit UKM, 2008)
A corollary of the electronic era in the area of electronic lexicography is the development and use of electronic dictionaries in language learning. This paper is concerned with the identification and examination of dictionary features perceived as helpful by ESL learners in assisting them in a sense differentiation task. Anecdotal data were analysed through a process of data reduction, data display and conclusion drawing and verification (Miles & Huberman, 1994). Qualitative coding categorization was adopted to classify and categorize media-related and generic-related dictionary features at three levels; macrostructural level, microstructural level, and interstructural level. Results generally indicated that preferred dictionary features mostly occurred at the microstructural level and that generic-related features were a priority as compared to media-specific features.